Commentary: Mind, Brain, and Education: The Impact of Educational Neuroscience on the Science of Teaching (LEARNing Landscapes, 2011)
Researchers have now acquired so much information about how the brain learns that a new academic discipline has been born, called "educational neuroscience" or "mind, brain, and education science." This field explores how research findings from neuroscience, education, and psychology can inform our understandings about teaching and learning, and whether they have implications for educational practice. This interdisciplinary approach ensures that recommendations for applying these findings to instructional practices have a foundation in solid scientific research. It also ensures that teachers are working smarter, not harder. This article discusses some of those exciting applications.
Keywords: brain; educational neuroscience; neuroscience; education; psychology; practice; interdisceplinary